MASTALGIA - Dwi Andhayani Kartikaputri; Ketut Widiana (E-Jurnal Medika Udayana, 2014)
Mastalgia is painful symptoms in the absence of abnormalities in the breast physiologyand pathology of the breast parenchyma. More than 80% of all cases mastalgia is a mildcase. The exact causes of mastalgia has not yet been sufficiently studied, but few studiesrelate endocrine abnormalities, inflammation, pcyconeurosis, improper nutrition, andconsumption of certain drugs. Based on the occurrence, mastalgia divided into twocategories, namely mastalgia cyclic (related to the endocrine system) and mastalgianoncyclic (associated with the nonendokrin system). Noncyclic mastalgia conditionscan be divided into two categories, which comes from the breast (true noncyclic breastpain) and in addition breasts (extramammary pain). Each classification of mastalgia hadtypical clinical picture, so the majority mastalgia diagnosis can already be diagnosedthrough a complete clinical examination. The most important of mastalgia managementis reassurance. This method will greatly affect the psychology of patients and areassociated with the severity of symptoms and response to therapy received by patients. 1 Non-pharmacological and pharmacological therapies may be done in accordance withthe indications. Surgical treatment is not recommended unless there is a definiteindication.